Y chromosome haplotype distribution of brown bears (Ursus arctos) in Northern Europe provides insight into population history and recovery - Schregel, Julia; Eiken, Hans Geir; Grøndahl, Finn Audun; Hailer, Frank; Aspi, Jouni; Kojola, Ilpo; Tirronen, Konstantin; Danilov, Piotr; Rykov, Alexander; Poroshin, Eugene; Janke, Axel; Swenson, Jon E.; et al.
2015